2013
DOI: 10.2478/s11658-012-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs: fine tuning of erythropoiesis

Abstract: Cell proliferation and differentiation is a complex process involving many cellular mechanisms. One of the best-studied phenomena in cell differentiation is erythrocyte development during hematopoiesis in vertebrates. In recent years, a new class of small, endogenous, non-coding RNAs called microRNAs (miRNAs) emerged as important regulators of gene expression at the post-transcriptional level. Thousands of miRNAs have been identified in various organisms, including protozoa, fungi, bacteria and viruses, provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Nonetheless, the implication of Nrf2-regulated miRNAs in anti-stress machinery is largely undefined. Mounting data demonstrate that miRNAs play important roles in directing erythropoiesis [31,33]. For instance, mice with deficiency of miR-144 and miR-451 showed such pronounced phenotypes as impaired late erythrocyte maturation, causing anemia and erythroid hyperplasia coupled to splenomegaly [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the implication of Nrf2-regulated miRNAs in anti-stress machinery is largely undefined. Mounting data demonstrate that miRNAs play important roles in directing erythropoiesis [31,33]. For instance, mice with deficiency of miR-144 and miR-451 showed such pronounced phenotypes as impaired late erythrocyte maturation, causing anemia and erythroid hyperplasia coupled to splenomegaly [65].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that miRNAs contribute to regulating erythropoiesis, and a few miRNAs are involved in erythropoiesis including proliferation of erythroid precursors, fetal γ-globin expression and enucleation [31][32][33][34]. It was also reported that miR-451 targeted 14-3-3zeta to activate FoxO3 pathway to protect erythroid cells from oxidant stress [35].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-96 is known for its abundance in adult blood reticulocytes, where it decreases γ-globin expression typical of fetal hemoglobin (α2γ2) allowing for the predominance of adult hemoglobin (α2β2) when reticulocytes mature into erythrocytes [32,33]. As a consequence of that, miRNA-96 silencing induces an increase in γ-globin [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of that, miRNA-96 silencing induces an increase in γ-globin [32,33]. In addition, overexpression of miRNA-96-5p inhibits autophagy and apoptosis in human breast cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, some more recent studies suggest that the latter is the more common mechanism for miRNA regulation [41]. They have been linked to a number of cellular processes, including apoptosis [42], inflammatory responses [43] and erythropoesis [44]. However, we are just beginning to understand their impact on cellular stress responses, such as hypoxia [45,46], oxidative stress [47,48], and various types of UPR activation, including insulin secretion [49] and B-cell differentiation [50].…”
Section: Micrornasmentioning
confidence: 99%